Development and delivery of a physiotherapy intervention for the early management of whiplash injuries: the Managing Injuries of Neck Trial (MINT) Intervention. - Williamson, E; Williams, M; Hansen, Z; Joseph, S; Lamb, S (2009)
This paper describes the development and implementation of a physiotherapy intervention for a large multicentred randomised controlled trial of the early management of whiplash injuries in a National Health Service setting. Participants were eligible if they were classified as having whiplash-associated disorder grades I to III and self-referred for treatment within 6 weeks of injury. The intervention development was informed through a variety of methods including the current evidence base, published guidelines, clinician opinion, a pilot study and expert opinion. The intervention was targeted at known, potentially modifiable risk factors for poor recovery, and utilised manual therapy, exercises and psychological strategies. The treatment was individually tailored, with a maximum of six treatments allowed within the trial protocol over an 8-week period. The intervention was delivered to 300 participants. The amount and types of treatments delivered are described.